Facilitating the retention of higher-order thinking skills in mathematics through Minecraft-based learning - Rayner Tangkui (UNION : Jurnal Ilmiah Pendidikan Matematika, 2024)
There is a growing need for students not only to develop higher-order thinking skills (HOTS) but also to retain them. Retaining HOTS enables students to effectively apply these skills when needed, particularly in solving complex problems in subjects like mathematics. However, many students struggle to retain these skills due to the prevalence of conventional teaching methods in classrooms. Therefore, this research aims to examine the impact of Minecraft-based learning in mathematics on the retention of HOTS. Using purposive sampling, 33 Year 5 primary school students from a single intact class were selected as participants. A test comprising 15 multiple-choice questions served as the research instrument, administered during the pretest, posttest, and delayed posttest. The data collected were analyzed using a one-way repeated measures ANOVA. The findings revealed that learning mathematics through Minecraft, a sandbox-style digital game set in an open world, significantly improved students' learning outcomes in both immediate and delayed assessments compared to their pre-assessment performance. Notably, the HOTS domain of analyzing showed the greatest improvement. These results suggest that incorporating Minecraft into mathematics instruction is particularly effective in enhancing and retaining HOTS.